Energy distribution and economic analysis of a residential house with the net-energy metering scheme in Malaysia - Norshahidatul Shahida Mohamed Suhaime; Shaikh Zishan Suheel; Ahmad Afif Safwan; Hasila Jarimi; Mohd Faizal; Adnan Ibrahim; Sohif Mat; Ahmad Fazlizan (Institute of Advanced Engineering and Science, 2022)
Malaysia demonstrates its commitment to alleviating the negative climate and energy issues through various initiatives. One of the latest initiatives is the amendment of the net-energy metering (NEM) scheme that takes effect from 2019. This paper presents the distribution of energy to the residential house that has a grid-connected solar photovoltaic (PV) system installed. The study quantifies the percentage of energy consumed from the PV system and the grid as well as the percentage of PV generated energy that is exported to the grid. On average, 38% of generated energy was used for self-consumption that contributed to 28% of the total consumption. Economic evaluation over a 25-year lifecycle of the PV system is also conducted shows that the simple payback period for NEM 2019 and NEM 2016 is 8 years and 20 years, respectively. The latest version of NEM shows a superior advantage compared to the previous one which may attract more investments in PV generation.